Redundancy and robustness in memory protection - Lampson, Butler (Proc. IFIP Cong, 1974)
The control of access to memory is a major problem in the design of protection mechanisms, especially for systems which allow files to be mapped into addressable memory. We use an abstract model of memory addressing to explain the space of possible organizations and examine their implications for protection. Analysis of the access paths to data allows some conclusions to be drawn about the amount of redundancy in a memory addressing scheme, and the possible consequences of an error for the integrity of the protection system.